Bioinformatics and Functional Genomics - Jonathan Pevsner (Wiley India Pvt. Ltd., 2015)
In this broad-based introduction Jonathan Pevsner presents the background theory to bioinformatics. Each chapter includes a problem set, pitfalls, boxes explaining key techniques and mathematics/statistics principles, summary, recommended reading, and a list of freely available software.